Application of HAZOP and What-If safety reviews to the petroleum, petrochemical and chemical industries - Nolan, Dennis P. (Noyes Publications, 1994)
This publication is intended to provide guidance to HAZOP (Hazard and Operability) and What-If review teams associated with the petroleum, petrochemical, and chemical industries. It describes the nature, responsibilities, methods, and documentation required in the performance of such reviews. This ensures the reviews are conducted in a timely, effective and professional manner as may be prescribed by a company's Process Safety Management (PSM) Policy. This book can be used as a practical reference to prepare the safety review requirements for these industries and their process safety management systems.
Keywords: Chemical engineering -- Safety measures.; elektronické knihy; electronic books